2014
DOI: 10.1007/s12031-014-0392-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphometric Comparison of the Molar Teeth in Pre-eruptive Developmental Stage of PACAP-Deficient and Wild-Type Mice

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a pleiotropic neuropeptide with widespread distribution. It plays pivotal role in neuronal development. PACAP-immunoreactive fibers have been found in the tooth pulp, and recently, it has been shown that PACAP may also play a role in the regeneration of the periodontium after luxation injuries. However, there is no data about the effect of endogenous PACAP on tooth development. Ectodermal organogenesis including tooth development is regulated by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 73 publications
(77 reference statements)
2
21
1
Order By: Relevance
“…We found that addition of PACAP elevated the deposition of inorganic matrix components in the ECM of UMR-106 cells [16]. Moreover, an altered mineralization was detected during tooth formation of PACAP deficient mice [94], suggesting a yet unknown connection between PACAP and Ca 2+ release of osteoblasts, ameloblasts and/or odontoblasts. As a possible mechanism for PACAP induced extracellular Ca 2+ accumulation during osteogenesis, calcitonin gene-related protein was proved to effect on osteoclast function [95] and the presence of PACAP decreased the matrix-resorption and consequent Ca-release by these cells [96,97].…”
Section: Vip and Pacap In Osteogenic Signaling Cascadesmentioning
confidence: 74%
“…We found that addition of PACAP elevated the deposition of inorganic matrix components in the ECM of UMR-106 cells [16]. Moreover, an altered mineralization was detected during tooth formation of PACAP deficient mice [94], suggesting a yet unknown connection between PACAP and Ca 2+ release of osteoblasts, ameloblasts and/or odontoblasts. As a possible mechanism for PACAP induced extracellular Ca 2+ accumulation during osteogenesis, calcitonin gene-related protein was proved to effect on osteoclast function [95] and the presence of PACAP decreased the matrix-resorption and consequent Ca-release by these cells [96,97].…”
Section: Vip and Pacap In Osteogenic Signaling Cascadesmentioning
confidence: 74%
“…We have reported that the inorganic matrix components of UMR-106 cell line can be elevated by PACAP addition [ 14 ]. Moreover, an altered mineralization was detected during tooth formation of PACAP defi cient mice [ 10 ], suggesting a yet unknown connection between PACAP and mineralized tissue formation. As a possible mechanism for PACAP induced extracellular Ca 2+ accumulation during osteogenesis, calcitonin gene-related peptide was proven to infl uence osteoclast function [ 105 ] and the presence of PACAP decreased the matrix-resorption and consequent Ca-release by these cells [ 90 , 106 ].…”
Section: Bone Formation Under the Control Of Vip And Pacap Signallingmentioning
confidence: 92%
“…20.2 ). In PACAP KO mice, enhanced SHH signalling was detected during tooth development [ 10 ]. On the contrary, exogenous administration of PACAP elevated the expression of SHH and a more pronounced nuclear presence of Gli1 was found in rat UMR-106 cells [ 14 ].…”
Section: Bone Formation Under the Control Of Vip And Pacap Signallingmentioning
confidence: 97%
See 2 more Smart Citations